Development of Audit Energy Application for Residential Sector - Rihartanto Rihartanto; Wawan Kustiawan; Lambang Subagiyo (Science and Technology Indonesia, 2018)
The residential sector is the biggest electric energy user in Indonesia. In this sector, there is a potential electricity saving of up to 30%. This savings can be obtained by implementing energy conservation. Energy use intensity (EUI) is a measure in assessing the efficiency of a building. From the EUI value can then be determined the efficiency criteria of a residential building, is it very efficient, efficient, moderately efficient or wasteful. An energy audit application was developed to facilitate in assessing the efficiency of a residential building in consuming electricity. The efficiency assessment in the model building shows that there is a significant electricity saving after the conservation efforts conducted, even though the model building is included efficient in the use of electrical energy.